Green Marketing and Consumer Awareness: Exploring the Link between Environmental Responsibility and Brand Value - Windarsari, Wiwin Riski (Malaqbi Publisher, 2025)
This study explores how consumers interpret green marketing efforts and how these interpretations shape their perceptions of environmental responsibility and brand value. The topic is important because growing environmental concerns and rising consumer demand for sustainability require companies to communicate their ecological initiatives clearly and authentically. However, issues such as greenwashing and vague environmental claims continue to create skepticism, making it necessary to understand how consumers assess the credibility of such messages. Using qualitative methods, including in-depth interviews and focus group discussions, this research investigates the cognitive, emotional, and social processes involved in consumer evaluations of green marketing. The findings indicate that authenticity, clarity, and evidence-based communication are essential for building consumer awareness and trust. Consumers respond positively to brands that demonstrate transparent, measurable environmental commitments and negatively to those perceived as exaggerating or misrepresenting sustainability claims. The study also reveals that emotional and ethical resonance strengthens brand loyalty, while social media discourse influences perceptions of credibility. These results highlight the importance of integrating environmental responsibility into brand strategy and ensuring transparent communication to enhance brand value. Overall, the research emphasizes that authentic sustainability practices are crucial for shaping informed, trusting, and loyal consumers.